Limit of acceptable change and recreation opportunity spectrum as a tool in developing a management plan: a study in Templer Forest Eco Park & Templer Forest Reserve / Syahidah Hanani Hamdan - Hamdan, Syahidah Hanani; Sabri, Nur Sabrina; Zakaria, Muhammad Hazim; Asri, Khairul; Kamal, Syanizatul Izreen; Roslan, Nor Asma Safuraa; Jamaluddin, Ely Rouzee; Kamarul Bahrain, Nawfal (2021)
The Management Plan of Templer Forest Eco Park and Templer Forest Reserved is constructed within the subject of managerial, social, and physical elements. Templer Forest Eco Park is managed by Majlis Perbandaran Selayang, meanwhile Templer Forest Reserved is owned and managed by Jabatan Perhutanan Negeri Selangor. The aim of this plan is to establish healthy and sustainable ecoforest and forest reserves that are well managed and cared which eventually will bring benefit to visitors and community. To do so, on site information was collected during technical visits, interview session, assessment of relevant documents and guideline as well as webinar sessions with major stakeholder have been conducted. In addition, this study employs theoretical and analytical approaches as its methodology. A total of 30 visitors, several representative from local community and local busines were reached out where their opinions were recorded and considered in the development of this Management Plan. A set of Issues, Concerns and Opportunities (ICO) were identified soon after. This plan is continued by the adaptation of Limit Acceptable Change (LAC) and Recreation Opportunity Spectrum (ROS) as approach to solve the issues, hence, the provision of two alternatives in Chapter 6 to identify the opportunities and limits. If an area did not manage to fulfil certain standards, then, the management must take actions to improve the situation. Apart from that, this Management Plan also reflects the new norms of Pandemic Covid-19 that the whole world has begun experiencing since early of 2020 by implementing the Standard Operating Procedure (SOP). To sum up everything, this Management Plan will serve as a roadmap for relevant stakeholders, particularly Majlis Perbandaran Selayang and Jabatan Perhutanan Negeri Selangor during the implementation of proposed actions. This management plan is hoped to bring changes to the future eco-tourism industry, as well as guide for future references.